PENERAPAN CSR DI PERUSAHAAN PERTAMBANGAN DAN PEMBANGUNAN EKONOMI BERKELANJUTAN DI KALIMANTAN SELATAN (Fakultas Ekonomi Universitas 17 Agustus 1945 Surabaya, Indonesia, 2022)
Corporate Social Responsibility (CSR) is the process of communicating the social and environmental impact of a company's economic actions within a particular community group and in society as a whole. Sustainable development with a progressive business model defines a business concept that combines income and economic benefits with genuine social and environmental sustainability. Thus, sustainable development is related to CSR. CSR in Indonesia has been implemented by most companies in Indonesia but there are still many that are not on target. This study aims to determine the application of CSR in mining companies and sustainable economic development in South Kalimantan. This research is a descriptive research with a case study approach. The result of the discussion is that CSR has been implemented by mining companies in South Kalimantan. The programs that have been implemented are the provision of scholarships, MSME training, PAUD/ TK teacher training, student internship programs, and blood donations.